The Effect of Massage for Babies Aged 3-6 Months on Sleep Duration at Posyandu Melati 3, Jatiluhur District, Purwakarta Regency, Indonesia - Triya Puspitarati (HM Publisher, 2023)
The gentle touch and affection given during massage can create a sense of security and positive connection between parent and baby. Massage can also help relieve physical discomfort your baby may be experiencing, such as bloating or teething. When babies feel better physically, they may sleep better. Baby massage can stimulate the baby's sensory system. This can help their sensory development and provide positive experiences related to touch and body feelings. This study aimed to determine the effect of massage for babies aged 3-6 months on sleep duration at Posyandu Melati 3, Jatiluhur District, Purwakarta Regency, Indonesia. This study is experimental research with a pre-post-test approach with control group and uses primary data, namely measuring the length of sleep of babies aged 3-6 months. A total of 30 research subjects took part in this study. In the intervention group, it was found that the majority of babies slept in the range of 14-16 hours, which is considered a normal duration. Meanwhile, the majority of the control group had a duration of less than 14 hours, which is classified as a short sleep duration. In conclusion, there is an effect of massage for babies aged 3-6 months on sleep duration at Posyandu Melati 3, Jatiluhur District, Purwakarta Regency, Indonesia.